UNIVERSITY NOTES. (The Accounting Review, 1940)
Abstract The article presents information about various activities taking place in various universities in the U.S. Professor R.D. Swick, R.E. Strohelm and D. Thompson are leaving the staff committee of the Indiana University. Professor John G. Blocker of the University of Kansas has taken a year's leave of absence in order to teach at the University of California, Berkeley, as visiting professor of accounting. Associate professor of accounting R.D.M. Bauer in the University of Missouri is absent on leave for one year. Professor H.K Olson of the University of South Dakota has received his Certified Public Accountants (CPA) certificate recently. Professor T.W. Leland of Agricultural and Mechanical College of Texas was re-elected as secretary-treasurer of the Texas Society of CPA's. Leland will continue as editor of the journal The Texas Accountant. Professor J.R. Taylor has accepted a position at the University of Tennessee. Professor R.K. Mautz passed the Illinois CPA examination in November 1939.